The Effect of Interleukin-6 and Tumor Necrosis Factor-Alpha Gene Polymorphism and Hormone Replacement Therapy on Polycystic Ovary Syndrome - Azeez, Sarhang Hasan; Ismail, Ismail Bilal; Darogha, Suhaila Nafia (Cellular and Molecular Biology, 2022)
PCOS (polycystic ovarian syndrome) is a prevalent and complicated gynecological endocrine disease that affects around 6% to 10% of women of reproductive age. PCOS is marked by oligoanovulation or anovulation, hyperandrogenism, hyperinsulinemia, monthly irregularity, and infertility. This study included 58 Kurdish females with PCOS who went to private clinics at Hawler city. The disease was confirmed by the doctors with laboratory results and US checking. They were at different age groups with different marital statuses. Demographic distribution, hormonal level and hormone replacement therapy were measured. Cytokine gene polymorphisms were evaluated by Single nucleotide polymorphism (SNP). The amplification-refractory mutation system (ARMS) was used to determine the gene polymorphisms. There was a significant change in the hormone levels and the medications as hormone replacement therapy gained best results for impregnation of the patients by Progyluton, Diane35 with metformin. Results of genetic variations in the evaluated cytokines revealed that for IL-6-174GC polymorphism the CC genotype was considered as a risk factor with OR:1.58, CI:0.16-15.36. While for TNF-α the higher producer GG genotype was the most susceptible cause of the disease with OR:1.41, CI: 0.59-3.36. Data of this study indicated the positive relationship between IL-6 -174GC polymorphism with PCOS while no association was detected for TNF-α -308GA.